THE INFLUENCE OF SATISFACTION AND E-WOM ON REUSE INTENTIONS MEDIATED BY BRAND TRUST(Study of Ruangguru Tutoring Students in Denpasar City) - Siwi Manganti; Ni Wayan Sri Suprapti, I Gst. A. Kt. Gd. Suasana, I Putu Gde Sukaatmadja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Indonesia is a country that has challenges in improving the quality of education, therefore there is a need for initiatives from the private sector to improve the quality of education. Ruangguru is present as an online and offline tutoring service, aiming to improve education in Indonesia so that it is better than before. This research aims to examine the influence of student satisfaction and the positive influence of electronic word of mouth (E-WOM) on students' reuse intention. Ruangguru tutoring, by considering the role of brand trust in the city of Denpasar. The population in this research are all Ruangguru students located in Denpasar City with a sample of 160 respondents through non-probability sampling. Data were collected using a questionnaire in the form of a Google form, data were processed using SEM-PLS using SmartPLS Version 3 software. The results of the analysis showed that satisfaction had a positive and significant effect on reuse intention and brand trust, E-WOM had a positive and significant effect on reuse intention and brand trust, and brand trust is able to mediate the effect of satisfaction and E-WOM on reuse intention.